THE MUHAMMADIYAH AS EDUCATION MOVEMENT - Elihami, Elihami; Basir, Rahmawati (Al-Mirah: Jurnal Pendidikan Islam, 2020)
The journey of Muhammadiyah in the field of education has given many contributions to education which has contributed a lot in educating the nation. This researcher will describe the role and contribution of KH. Ahmad Dahlan and the organizations he founded namely Muhamadiyah in accompanying the long journey of education in Indonesia. Muhammadiyah as a civil society, in its vision emphasizes the function of carrying out as the role of the state in its vision emphasizing the function of carrying out as the role of the role of the state. in the social field, Muhammadiyah established various orphanages, and Muhammadiyah also attended the development of educational institutions.